Effects of COVID-19 on dietary behavior of urban consumers in Nairobi, Kenya - Chege, Christine G. K.; Onyango, Kevin; Kabach, Joram; Lundy, Mark (Frontiers in Sustainable Food Systems, 2022)
The disruptions wrought by the COVID-19 pandemic on food systems worldwide have endangered food and nutrition security for many consumers. The resource-poor, especially those in urban areas, are more susceptible to pandemic-related disturbances. This study uses primary data collected from 2,465 households located in and outside of informal settlements (slums) in Nairobi, Kenya to assess how Covid-19 and related public-health measures have influenced diets of urban consumers, their purchasing patterns and overall food security. Questions about food security and consumption behavior, including household dietary diversity scores, were used to capture the pre- and mid-pandemic situation. The data show that low-income households in the informal settlements were more affected than middle-income households. About 90% of slum households reported dire food insecurity situations, including being unable to eat preferred kinds of food, eating a limited variety of foods, consuming smaller portions than they felt they needed, and eating fewer meals in a day. With a score of four food groups out of nine, household in the informal settlements have lower dietary diversity than middle-income households, whose score is five out of nine. The consumption of nutritious foods, including fruits, vegetables, and animal products, fell among people living in slums during the pandemic. In addition to assessing dietary changes, this study highlights the factors associated with quality food consumption during the pandemic period such as household income levels and male-vs-female headed households. Our research demonstrates the need to attend to slums and vulnerable, poor consumers when enacting mitigation measures or designing and implementing policy. Keywords: COVID-19, urban poor consumers, consumption, nutrition, Africa, Kenya